Policy Advocacy for Strengthening Village Governance in Developing Tourism Destination in Wangunharja Village - Pradesa, Hafid Aditya; Zulvia, Pepi; Syawali, Andi Zhillan Sabtina (IMPOWERMENT SOCIETY, 2022)
The development of tourism villages has become one of important programs of current government. Wangunharja Village, one of area in Lembang District, West Bandung Regency in West Java, has tourism potential that can be developed by stakeholders. The implementation of this community service activity uses the focus grup discussion method in order to increase understanding and involvement among stakeholders of the Wangunharja Village. The subject of the intense discussion with the Village Community was about understanding strengthening social capital in the process of developing tourism destinations. As a result, community gave a positive response and expressed their commitment in strengthening social capital such as form of collective action for managing resources in their area. This subject condition will be followed up by the Wangunharja Village Government by developing policies that encourage positive affirmations that could lead to more involvement among village communities. This activity recommends further activities in the form of workshops to guide the community in the process of developing tourism destinations in a sustainable manner.